PENYULUHAN PRANIKAH BAGI REMAJA DESA KUNTI, ANDONG, BOYOLALI - Yahya Ibadurrahman; S Syamsuddin; Restu Ramadhan (AL HAZIQ: Journal of Community Service, 2025)
This Community Service Program (PKM) aims to enhance the understanding of adolescents in Kunti Village, Andong Subdistrict, Boyolali Regency regarding premarital readiness, the risks of early marriage, and the importance of future planning. The program was conducted using a participatory approach involving 40 adolescents as active participants through discussions, case studies, and interactive Q&A sessions. The educational materials covered mental readiness, reproductive health, partner communication, and the social and economic consequences of early marriage. The results indicate a significant increase in adolescents’ awareness of health risks and long-term implications associated with early marriage, along with a shift toward more deliberate future planning. Participants also demonstrated improved ability to identify potential conflicts and apply effective communication strategies before entering marriage. Although challenges such as social pressure and limited access to reproductive health information persisted, the program had a positive impact on premarital literacy among youth in the village. Overall, this PKM activity provides a crucial foundation for strengthening sustainable premarital education at the community level.